Osteoblastoma of the temporal articular tubercle misdiagnosed as a temporomandibular joint disorder. Issue 5 (May 2017) - Emanuelsson, J.; Allen, C.M.; Rydin, K.; Sjöström, M.
Abstract: The case of a 17-year-old female with a benign osteoblastoma in the temporomandibular joint (TMJ) is reported. The patient had a 2.5-year history of reduced mouth opening accompanied by tenderness and swelling in the left TMJ. Initial treatment included stabilization of the occlusion with a splint, jaw exercises, and analgesics. At first the patient's symptoms decreased, but they then increased 18 months later, prompting a cone beam computed tomography (CBCT) evaluation of the joint. The radiographic findings showed a somewhat ill-defined, radiolucent, expansile lesion containing small scattered calcifications located in the temporal articular tubercle. The lesion was removed under general anaesthesia and sent for histopathological examination. At the 12-month follow-up, the patient had normal TMJ function without clinical symptoms. CBCT examination showed a small recurrence of 3 mm. Another 12 months later, CBCT showed a 1-mm increase in the recurrence. Her function was normal, with slight tenderness lateral to the left TMJ. The decision from a multidisciplinary meeting was further annual follow-up. The present case illustrates the importance of initial radiographic examination together with clinical examination in patients with TMJ dysfunction.